On the ubiquity of drug selling among youthful offenders in Washington, D.C., 1985–1991: Age, period, or cohort effect? - Saner, Hilary (Journal of quantitative criminology, 1995)
We present a multiple-cohort analysis of rates of participation in drug offenses versus other crime in an urban sample, based on official charge data on young adults from the Pretrial Services Agency in the District of Columbia for the years 1985 to 1991. We make lower-bound estimates of how many individuals from particular population groups residing in the District are involved in drug-related criminal activities, examine trends in drug and nondrug charges in Washington, D.C., and disentangle the age, cohort, and period effects in the variation in participation in drug offenses across multiple birth cohorts in the city. We estimate that up to 30% of the young, black male populationof the District of Columbia were charged with drug distribution during this time. Charge rates for drug distribution activities appear to peak around age 24, decreasing slowly thereafter. Large and nonlinear period effects were observed for all drug-related charge rates, while increasing linear period effects were found for nondrug misdemeanors. Cohort effects in drug-related charge rates were also observed. Levels of participation in drug distribution charge rates were lower for older cohorts, while the cohort share with a drug possession charge declined for younger cohorts. However, when age and period effects are included in the models, these cohort effects are muted or disappear, except in the case of nondrug misdemeanors.